2020
DOI: 10.1073/pnas.1920122117
|View full text |Cite
|
Sign up to set email alerts
|

TPC1 deficiency or blockade augments systemic anaphylaxis and mast cell activity

Abstract: Mast cells and basophils are main drivers of allergic reactions and anaphylaxis, for which prevalence is rapidly increasing. Activation of these cells leads to a tightly controlled release of inflammatory mediators stored in secretory granules. The release of these granules is dependent on intracellular calcium (Ca2+) signals. Ca2+ release from endolysosomal compartments is mediated via intracellular cation channels, such as two-pore channel (TPC) proteins. Here, we uncover a mechanism for how TPC1 regulates C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…The study also found that TPC1 modulation either by genetic deletion or by pharmacological inhibition by trans -Ned-19 augmented mastocyte degranulation and evoked the release of inflammatory mediator (histamine) from mast cells ( 9 ), which are tissue-resident cells of the immune system that play a role in inflammatory and allergic reactions. The number and the size of the mastocytes were significantly attenuated in the TPC1-deficient murine model compared to WT controls ( 9 ). The cellular mechanisms underlying the regulation of TPC1-mediated endolysosomal Ca 2+ signals in the development of inflammatory and allergic reactions warrants further investigation to aid the development of new drugs for the treatment of anaphylaxis and allergic hypersensitivity.…”
Section: Tpcs In Phagocytosis Inflammatory Response and Virus Traffickingmentioning
confidence: 82%
See 4 more Smart Citations
“…The study also found that TPC1 modulation either by genetic deletion or by pharmacological inhibition by trans -Ned-19 augmented mastocyte degranulation and evoked the release of inflammatory mediator (histamine) from mast cells ( 9 ), which are tissue-resident cells of the immune system that play a role in inflammatory and allergic reactions. The number and the size of the mastocytes were significantly attenuated in the TPC1-deficient murine model compared to WT controls ( 9 ). The cellular mechanisms underlying the regulation of TPC1-mediated endolysosomal Ca 2+ signals in the development of inflammatory and allergic reactions warrants further investigation to aid the development of new drugs for the treatment of anaphylaxis and allergic hypersensitivity.…”
Section: Tpcs In Phagocytosis Inflammatory Response and Virus Traffickingmentioning
confidence: 82%
“…In the in vivo TPC1KO murine model, systemic anaphylaxis was exaggerated, manifested by a profound drop in body temperature compared to WT mice ( 9 ). The study also found that TPC1 modulation either by genetic deletion or by pharmacological inhibition by trans -Ned-19 augmented mastocyte degranulation and evoked the release of inflammatory mediator (histamine) from mast cells ( 9 ), which are tissue-resident cells of the immune system that play a role in inflammatory and allergic reactions. The number and the size of the mastocytes were significantly attenuated in the TPC1-deficient murine model compared to WT controls ( 9 ).…”
Section: Tpcs In Phagocytosis Inflammatory Response and Virus Traffickingmentioning
confidence: 99%
See 3 more Smart Citations